Ekstraksi Frekuensi dari Bunyi Alqurans dengan Metode Discrete Fourier Transform: Studi Kasus Bunyi QS. Al-Fatihah - Kusmiran, Amirin; Andi Syam Rizal; Sahara; Ahmad Zarkasi; Kasturi Ramadani (Universitas Islam Negeri Alauddin Makassar, 2024)
The Quran is a miracle received by the Prophet Muhammad. Alquran can use to reduce anxiety in patients with acute coronary syndrome, hemodialysis, schizophrenia, etc., when the sound retardation of this Qur'an, especially QS. Al-Fatihah. The physical properties of waves can be analyzed using the discrete Fourier transform method for frequency extraction. This method is scripted using the Python programming language. The results show that frequency in Qs. Al-Fatihah/1:1-7 are random in range 150 Hz – 800 Hz.Thus, the frequencies of the Quran, especially QS Al-Fatihah, are uneven waves that can cause harmonic vibrations against brain waves.